THE EFFECT OF APPLICATION OF VARIOUS FERTILIZERS ON COCOA PLANT GROWTH - Widyanto, Dwi; Kurniawan, Mokhamad Yanuar; Wahid, Akbar Abdul; Ningsih, Suci Setya; Ramadhani, Muhammad Dio (ITScience (Information Technology and Science), 2022)
Fertilizer divided becomes two, namely fertilizer organic and inorganic. According to USEPA, fertilizer organic is applied compost to plants as source nutrients. Fertilizer inorganic is fertilizer result of engineering process by chemical, physical and or biological and the results industry or factory maker fertilizer (Dewanto et al., 2013). Plant need fertilizer to reach production maximum. In research Roidah (2013) there is several of types of fertilizer the observed organic fertilizer cage contains 5 kg N, 3 kg P 2 O 5 and 5 kg K 2 O as well as other essential nutrients in relative amount small. This post aims to know the importance application fertilizer to growth plant cocoa. Based on some of the literature research described could be concluded that fertilizer inorganic and fertilizer organic have advantages as well as deficiencies in several parameters, namely content nutrients, duration nutrient availability, and cost. Application fertilizer inorganic takes to effect real to upgrade production plant cocoa faster and high but no sustainable whereas application fertilizer organic no take to effect real but sustainable. Then, the application of fertilizer on plants cocoa must be combined among fertilizer inorganic and fertilizer organic with composition certain. Application fertilizer inorganic and fertilizer organic in-unit tree plant cocoa need assessment more continue, study more carry on based on age, physiology, type soil, and method application. That thing is in tune with the condition geography in Indonesia which is an archipelagic country so every area has different traits.